NOWE STANOWISKO DIPLOSCHISTES MUSCORUM (Scop.) R. Sant. na NIZINIE WIELKOPOLSKO-KUJAWSKIEJ - Zarabska–Bożejewicz, Daria (Badania Fizjograficzne Seria B - Botanika, 2020)
Diploschistes muscorum (Scop.) R. Sant. has been found in the southern part of the Wielkopolsko-Kujawska Lowland. So far, in western and central Poland the species has been reported in few localities.